Mission Santa Clara after the fire - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows the debris of the Santa Clara Mission, destroyed by the October 1926 fire. Much of the edifice is obscured by smoke or fog. The blurred figures of men stand in the debris.